Exploring kinetic typography as an alternative medium in delivering messages / Nor Arseha Karimon - Karimon, Nor Arseha (2015)
Animated texts are derived from Kinetic Typography which symbolizes the strategy of the art of expression. Variation in Kinetic Typography is in its capability to add considerable emotive articles and empowering functions that are normally found in films. This includes set of words detailed in the spoken concept. Kinetic Typography is an important approach in visual communication when delivering messages and creating influence in educating and creating responsiveness visually. An objective of this research is to study the audiences' awareness on the use of Kinetic Typography in social society campaigns. Based on user and gratification approach, people used media for obtaining information and knowledge. Therefore, Kinetic Typography can be expected to be an important method in visual communication to deliver messages. This study provided eight samples of social community campaigns that used Kinetic Typography. They were then used to measure the acceptance level among the respondents. Questionnaire was administered via online application to measure the respondents' perception on Kinetic Typography. Samples were among 400 respondents from Multimedia University, mainly students and professional employees in the district of Melaka Tengah. Research findings showed that majority of the respondents agreed that Kinetic Typography approach gave better understanding in educating and creating awareness in visual communication. It also provided more input rather than just images. It is also show that the expression of the typefaces communicated some expression to deliver the message to its audience effectively. According to the research findings, appropriate typefaces exploitation during this video increased the meaning of the messages when Kinetic Typography was deployed and as such, perfectly deliver the messages as intended.